2021
DOI: 10.1021/acsomega.0c05488
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-Q-TOF/MS-Based Metabolomics Approach to Reveal the Hepatotoxicity of Emodin and Detoxification of Dihydromyricetin

Abstract: Dihydromyricetin (DMY), an important flavanone found in Ampelopsis grossedentata, plays a protective role in liver injury. Our previous research found that DMY protected L02 cells against hepatotoxicity caused by emodin. In this study, serum, urine, and liver samples from rats were systematically used for biochemical analysis, pathological observation, and nontargeted metabolomics to evaluate the toxicity of emodin and DMY intervention. After oral administration of DMY, DMY may alleviate liver injury by improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…15,16 Moreover, it has been used to study drug metabolism, [17][18][19][20][21][22] toxicokinetics, 23,24 lipidomics, 25,26 proteomics 27,28 and metabolomics. 29,30 The main advantage of mass spectrometry (MS/MS) is the ability to detect a broad range of drugs with high sensitivity and specicity in a single analytical run. [31][32][33][34] Chemical compounds are recognized by comparing their retention times and parent-daughter ions with those of reference substances.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Moreover, it has been used to study drug metabolism, [17][18][19][20][21][22] toxicokinetics, 23,24 lipidomics, 25,26 proteomics 27,28 and metabolomics. 29,30 The main advantage of mass spectrometry (MS/MS) is the ability to detect a broad range of drugs with high sensitivity and specicity in a single analytical run. [31][32][33][34] Chemical compounds are recognized by comparing their retention times and parent-daughter ions with those of reference substances.…”
Section: Introductionmentioning
confidence: 99%
“…DMY has been showed a protective effect from the emodin‐induced hepatoxicity on the normal human hepatic LO2 cells via the upregulation of Nrf2 and downregulation of CYP7A1 [98]. Besides, metabolomic results of another study revealed that DMY could also reversed the damage of emodin‐induced liver impairment in rats due to the regulation of 18 proteins as well as the metabolism of glutathione, pyrimidine, and tryptophan [110].…”
Section: Pharmacological Effects and Actions Mechanisms Of Dmymentioning
confidence: 99%
“…Here, we show that the lyPC(20:1) component for glycerophospholipid metabolism decreased with emodin and reversed with silybin treatment. This suggests that silybin could have liver protective effects by regulating appropriate glycerophospholipid metabolism, which was also found for dihydromyricetin (Gao et al, 2021). Again, additional targeted metabolomics research on glycerophospholipid metabolism is required to explain the exact cellular processes for hepatoxicity.…”
Section: Silybin-treated Serum Biochemistry and Liver Histopathology ...mentioning
confidence: 84%
“…The rats were divided into three groups (n = 8, each). Group I (control) rats were orally administered an equal volume of distilled water; group II (model) rats were orally administered 1500 mg/kg of emodin every other day (q2D) for 4 weeks; and group III (silybin) rats were orally cotreated with 1500 mg/kg of emodin (Gao et al, 2021;X. Yang et al, 2018) and 100 mg/kg of silybin q2D for 4 weeks (Sun et al, 2020;B.…”
Section: Animals Treatment and Tissue Collectionmentioning
confidence: 99%
See 1 more Smart Citation